Evaluating the therapeutic role of selected active compounds in Plumula Nelumbinis on pulmonary hypertension via network pharmacology and experimental analysis - Xinghua Xiao; Xinghua Xiao; Xinghua Xiao; Fangmei Luo; Minyi Fu; Minyi Fu; Minyi Fu; Yueping Jiang; Yueping Jiang; Yueping Jiang; Shao Liu; Shao Liu; et al. (Frontiers Media S.A., 2022)
Excessive proliferation and migration of pulmonary artery smooth muscle cells (PASMCs) are critical factors leading to vascular remodeling in pulmonary hypertension (PH). This study aimed to explore the effect and potential mechanism of Plumula Nelumbinis on PH by using network pharmacology and experimental analysis. Network pharmacology and molecular docking results indicated that the potential active components of Plumula Nelumbinis against PH were mainly alkaloid compounds, including neferine, liensinine, and isoliensinine. Subsequently, by constructing a Su5416 plus hypoxia (SuHx)-induced PH rat model, we found that the total alkaloids of Plumula Nelumbinis (TAPN) can reduce the right ventricular systolic pressure, delay the process of pulmonary vascular and right ventricular remodeling, and improve the right heart function in PH rats. In addition, TAPN can effectively reverse the upregulation of collagen1, collagen3, MMP2, MMP9, PCNA, PIM1, and p-SRC protein expression in lung tissue of PH rats. Finally, by constructing a hypoxia-induced PASMCs proliferation and migration model, we further found that TAPN, neferine, liensinine, and isoliensinine could inhibit the proliferation and migration of PASMCs induced by hypoxia; reverse the upregulation of collagen1, collagen3, MMP2, MMP9, PCNA, PIM1 and p-SRC protein expression in PASMCs. Based on these observations, we conclude that the alkaloid compounds extracted from Plumula Nelumbinis (such as neferine, liensinine, and isoliensinine) can inhibit the abnormal proliferation and migration of PASMCs by regulating the expression of p-SRC and PIM1, thereby delaying the progression of PH.